Sports schools and the creation of champions: following 10 female handballers for a decade - Kristiansen, E.; Stensrud, T. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
The number of secondary sport schools and high schools in Norway is increasing and presumably resulting in earlier sport specializing and increased training volume among the young athletes. How do the athletes respond to the total load? The sport school system can be a valuable resource to develop for young aspiring athletes, in particular in national sport such as handball in Norway, but extra pressure is also put on young athletes that chase an Olympic dream. Methodology This qualitative multidisciplinary study, a combination of psychology, physiology and management, followed a group of 10 female student-athletes from the age of 13 to 23 to closely monitor their physical and mental development as well as their understandings of ups and downs at a sport school in Norway. The handballers also provided us with physical data so we could monitor their physical and psychological development. Thematic analysis was used for the complete data material, several measures was taken to protect the athlete`s anonymity in addition to ensure trustworthiness by prolonged engagement, reflexivity and discussion of results with participants and collegues. Results When we first started following them at age 13, the importance of sleep, growth and stage of puberty needs to be taken into consideration in the total workload. However, parental support, support from teachers/trainers at school and rest are mentioned as main coping mechanisms that contribute to effective coping. Evidence of competition-related stressors, organizational stressors (sport and school balance) and personal stressors (social life and sport balance, lack of sleep and severe injuries) was recurring themes in the annual interviews with the handballers. After ten years, only three were playing at the elite level. They had also taken part in the injury preventive program, they had stamina, and they always had a good relationship with their coach. However, all three had gone through serious long-lasting injuries, and their return to sport provided interesting information. This is necessary as talking about pain in the context of handball, where players are expected to be tough and push through pain, was hard. Discussion It is important to be aware that young athletes need time to adapt to a high workload, high expectations and the huge demands of elite sport. Together this will create a constant `need` to cope with new and different sources of strain. After a decade, importance of the coach-athlete relationships, emerged as a parallel narrative to that of injuries. Being seen was the common denominator for healthy and sustainable development among our participants. We would recommend teaching athletes in contact sports to talk about pain and injuries in order to protect them. This is vital to preventing them from developing long-term and career-ending injuries. To conclude, miscommunication or lack of communication and not feeling seen when they struggled where the reason why half of them ended their career prematurely.